ENHANCING DIVERSITY OF POULTRY PRODUCTS BY PRODUCING HIGH QUALITY BROWN EGGS - Hanan Al-Khalifa; Gehan Ragheb (European Scientific Journal, ESJ, 2013)
There has been interest in increasing egg production and enhancing diversity of poultry products in the state of Kuwait. The main objective of the current study is to investigate the differences between production performance between brown and white strains of laying hens. One day old pullets from Lohmann LSL-Classic and Lohmann Brown-Classic strains were used, 600 each. Food and water were provided ad libitum. Body weight, total feed consumption, overall feed efficiency, overall percent egg production, overall egg weight, overall egg mass, shell weight, and Haugh Unit (HU) were measured. Mortality, temperature and humidity were recorded daily. Data were analyzed using ANOVA. Means were separated using Tukey’s test where significance was set at P< 0.05. The results showed that overall body weight gain and feed efficiency for the brown pullets were significantly (P<0.05) better than the white pullets. Mass of eggs and feed efficiency in case of brown hens were significantly (P<0.05) higher than that of the white hens for the last period (58-69 wk of age). In general, the production performance of the Lohman brown strain was better than that of the LSL white strain. This could enhance diversity of poultry products in the country and provide consumers with high quality eggs.